2003
DOI: 10.1111/j.1745-9125.2003.tb00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Discretion and Disparity Under Sentencing Guidelines: The Role of Departures and Structured Sentencing Alternatives*

Abstract: This article examines the use of alternative sentencing provisions as mechanisms for departing from sentencing guidelines in Washington State and as structural sources of unwarranted sentencing disparity. The authors argue that these structural features of guidelines not only serve as “windows of discretion” through which disparities arise, but they also may encourage disparities by requiring consideration of substantive criteria that disadvantage certain offender groups. The analyses find that males and minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(173 citation statements)
references
References 27 publications
(24 reference statements)
9
150
0
Order By: Relevance
“…Engen and his colleagues (2003) concluded that race and/or ethnicity had significant yet mixed effects on upward departures. The odds that Hispanic defendants received an upward departure was 68% higher than the odds for white defendants, whereas the odds that black defendants received an upward departure was 35% lower than the odds for white defendants (Engen et al, 2003). Unlike Engen et al (2003), however, Johnson (2003) found that race positively affected upward departures.…”
Section: Research On Aggravated Sentencingmentioning
confidence: 64%
See 2 more Smart Citations
“…Engen and his colleagues (2003) concluded that race and/or ethnicity had significant yet mixed effects on upward departures. The odds that Hispanic defendants received an upward departure was 68% higher than the odds for white defendants, whereas the odds that black defendants received an upward departure was 35% lower than the odds for white defendants (Engen et al, 2003). Unlike Engen et al (2003), however, Johnson (2003) found that race positively affected upward departures.…”
Section: Research On Aggravated Sentencingmentioning
confidence: 64%
“…The odds that Hispanic defendants received an upward departure was 68% higher than the odds for white defendants, whereas the odds that black defendants received an upward departure was 35% lower than the odds for white defendants (Engen et al, 2003). Unlike Engen et al (2003), however, Johnson (2003) found that race positively affected upward departures. Johnson (2003) found that black defendants were more likely to receive an upward departure whereas Engen et al(2003) found that black defendants were less likely to receive an upward departure.…”
Section: Research On Aggravated Sentencingmentioning
confidence: 64%
See 1 more Smart Citation
“…Rather, it is simply an acknowledged limitation inherent to any analyses relying on official records. The same applies here as well as to any other empirical study of sentencing outcomes relying on official data (e.g., Engen, Gainey, Crutchfield, & Weis, 2003).…”
Section: Notesmentioning
confidence: 97%
“…Further studies have found that Latino offenders have significantly greater odds than nonLatino offenders of receiving an upward departure, but that African-American offenders tend to have lower odds than white offenders of receiving an upward departure, despite both AfricanAmerican and Latino offenders having significantly lower odds than white and non-Latino offenders, respectively, of receiving downward departures (Engen, Gainey, Crutchfield, Weis 2003).…”
Section: Focal Concerns and Extralegal Factors Influencing Sentencingmentioning
confidence: 99%